Enhancing Learning Outcomes in Explanation Texts through the Make a Match Model - Sutrisno, Trisno; Fecilita, Benfika Fiden; Thoyyibah, Luthfiyatun; Irawaty, Inna (English Teaching and Linguistics Journal (ETLiJ), 2025)
This classroom action research (CAR) examines the effectiveness of the Make a Match cooperative learning model in improving students' learning outcomes and motivation in understanding explanation texts. The study employed an experimental design with two classes of 11th-grade students (N=64) at a senior high school in Ciamis Regency: an experimental class (XI-A5) using Make a Match and a control class (XI-S1) using conventional methods. Quantitative data revealed significant differences in outcomes between the two approaches. The experimental class achieved higher average scores on both the pretest (81.88 vs. 75.63) and posttest (86.88 vs. 78.44) compared to the control group. Beyond academic improvement, observational data showed the Make a Match approach increased student engagement through its interactive card-matching activities, which fostered peer collaboration and active participation. These findings demonstrate that Make a Match is more effective than traditional lecture methods for teaching explanation texts, as it simultaneously enhances comprehension and motivation. For classroom implementation, teachers should: (1) integrate game-based elements to increase engagement, (2) design matching tasks that align with key learning objectives, and (3) use collaborative activities to reinforce critical thinking. This approach is particularly valuable in EFL contexts where students struggle with text-based learning, offering a practical strategy to combine academic achievement with motivational support.